Applying the R = MC2 implementation science heuristic to assess the impact of readiness on reach and implementation of a population‐wide genomic screening program. - Allen, Caitlin G.; Hunt, Kelly J.; Jackson, Amy; Baierl, Joseph; McMahon, Lori L.; Judge, Daniel P. (Journal of Genetic Counseling, 2024)
Population‐wide genomic screening for genes that have high penetrance and clinical actionability enhances the opportunity to identify individuals at risk for developing hereditary conditions. Organizational readiness has been shown to influence the likelihood of successful implementation of complex initiatives such as the integration of population‐wide genomic screening in clinical settings. We use the organizational readiness heuristic R = MC2 to better understand three factors that influence readiness for implementation of In Our DNA SC, a population‐wide genomic screening program: motivation to implement, general capacity of an organization, and innovation‐specific capacities. We then assessed the influence of these readiness factors on implementation outcomes of reach (measured through enrollment rate) and implementation (measured through the number of DNA samples collected). Data were collected pre‐implementation and captured during the three‐month pilot phase of the In Our DNA SC program. We collected administrative data from the electronic health record and quantitatively captured elements of readiness through surveys distributed to provider champions and clinical administrative champions at the 10 sites implementing the population‐wide genomic screening program. We facilitated innovation‐specific capacity through training offered at each site, as well as technical assistance through weekly meetings with other implementing sites, and resources available to all staff. Forty percent of provider champions attended training and 80% of administrative champions attended training. An average of 3.7 additional staff were trained at each implementing site. Satisfaction with training positively influenced reach (β = 0.0121, p = 0.0271) but did not impact implementation. Provider engagement (innovation capabilities) was associated with reach (β = 0.0020, p = 0.0251) and clinical administrator engagement was associated with sample collection rate (β = 0.2599, β = 0.038). Readiness to change is considered one of the most important factors in understanding the potential opportunity for implementation. We found that motivation to adopt a population‐wide genomic screening program positively impacted the program's reach. The type of champion influenced discrete outcomes, with provider champions positively impacting reach and administrative champions influencing implementation (assessed through sample collection rate). As genomics continues to be integrated into clinical practice, it will be important to understand the contextual factors that influence readiness for implementation and design support throughout the life‐course of implementation to ensure the success of large‐scale, complex initiatives.